2017
DOI: 10.1503/cmaj.160839
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental temperature on risk of gestational diabetes

Abstract: The impact of climate variability on health has become increasingly relevant given the global rise in air temperatures over the past century.1,2 Extreme weather patterns can adversely influence health -directly, as in the case of hyperor hypothermia -and indirectly, by triggering respiratory exacerbations, infectious outbreaks, water-borne diseases and injuries. However, there is also growing evidence supporting a link between air temperature, metabolic function and energy expenditure. Brown adipose tissue aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 34 publications
4
52
0
2
Order By: Relevance
“…Our finding that glucose levels in pregnancy varied with ambient temperature is in keeping with a number of previous studies [7,8,10,12,14,15] from various settings around the world. At hotter temperatures, the impact of a fixed glucose load may be greater due to reduced circulating plasma volume, leading to increased diagnoses of GDM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding that glucose levels in pregnancy varied with ambient temperature is in keeping with a number of previous studies [7,8,10,12,14,15] from various settings around the world. At hotter temperatures, the impact of a fixed glucose load may be greater due to reduced circulating plasma volume, leading to increased diagnoses of GDM.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to risk associated with individuals, however, there may also be factors in the general environment that influence the likelihood of GDM. Several recent reports suggest that GDM incidence varies with season in diverse settings including southern Europe [7][8][9], Brazil [10], Australia [11][12][13] and Canada [14,15]. These studies show that postload glucose values and incidence of GDM increase at higher ambient temperatures [7,8,10,13,14].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…9 Therefore another factor that could explain at least part of the increased incidence of GDM is exposure to raised or rising ambient temperatures in certain populations. [10][11][12] Following this some studies have reported seasonal variations in the incidence of GDM [13][14][15][16][17] , although this has not been observed in all populations or climates. 18,19 In this study we investigated whether there were temporal and seasonal trends in GDM incidence in our single centre population from Cambridge, U.K. which recruited pregnant women between 2001 and 2009.…”
Section: Introductionmentioning
confidence: 96%
“…1,2 This has been observed across the general population in the USA 3 and, in pregnant women in Canada relative to the onset of gestational diabetes. 4 Moreover, the prevalence of gestational diabetes in Canada is higher in the summer and rising ambient temperatures in the 3-4 weeks prior to third trimester glucose tolerance testing can predict gestational diabetes onset. 5 Consequently as brown fat is highly sensitive to changes in ambient temperature and is normally activated by cold exposure it would be expected to become less active as temperature rises.…”
mentioning
confidence: 99%